Kekerasan Bermotif Agama: Perspektif Fundamentalisme, Radikalisme, dan Ekstremisme - Nuraeni, Heni Ani; Salsabila, Salsabila; Dapfa, Agam Muhammad; Wardani, Reny Sukma (Peneliti.net, 2024)
Instead of viewing violence through the tired lens of